2020
DOI: 10.1101/2020.04.07.029090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Absence of SARS-CoV-2 infection in cats and dogs in close contact with a cluster of COVID-19 patients in a veterinary campus

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which originated in Wuhan, China, in 2019, is responsible for the COVID-19 pandemic. It is now accepted that the wild fauna, probably bats, constitute the initial reservoir of the virus, but little is known about the role pets can play in the spread of the disease in human communities, knowing the ability of SARS-CoV-2 to infect some domestic animals. We tested 21 domestic pets (9 cats and 12 dogs) living in close contact with their owners (belongin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 5 publications
2
26
0
1
Order By: Relevance
“…While our results are inconsistent with transfection studies using civet ACE2 receptors expressed in HeLa cells ( 1 ), these experiments have limitations as discussed above, and no data are available on infectivity in civet cells or animals. While carnivores closely related to dogs (dingoes, maned wolves, and foxes) all scored low, experimental data consistently show that dogs are not readily infected or symptomatic ( 45 , 60 , 66 ).…”
Section: Discussionmentioning
confidence: 98%
“…While our results are inconsistent with transfection studies using civet ACE2 receptors expressed in HeLa cells ( 1 ), these experiments have limitations as discussed above, and no data are available on infectivity in civet cells or animals. While carnivores closely related to dogs (dingoes, maned wolves, and foxes) all scored low, experimental data consistently show that dogs are not readily infected or symptomatic ( 45 , 60 , 66 ).…”
Section: Discussionmentioning
confidence: 98%
“…Animal susceptibility to infection by SARS-CoV-2 has been studied in vivo [18,19,50,51,57] and in vitro [20][21][22] during the course of the pandemic. Parallel in silico work has made use of the protein structure of the S-protein:ACE2 complex to computationally predict the breadth of possible viral hosts.…”
Section: Discussionmentioning
confidence: 99%
“…No positive cases were reported in dogs exposed to SARS-CoV-2 in France. 16 Another recent study in Italy carried out with pets has shown that none of the 817 animals studied was positive to SARS-CoV-2 by RT-qPCR test but 13 dogs and 6 cats had neutralizing antibodies. 13 In this manuscript we report that, during the months of the pandemic, an increase of aggressive lung pathologies in dogs was detected by veterinarians in Spain.…”
Section: Introductionmentioning
confidence: 93%